Hubungan Keimanan Dengan Imunitas Dalam Persfektif Hadis - Siregar, Nurmala Indah (UIN Sumatera Utara Medan, 2023)
This study discusses the quality of the Hadith about the morning prayer in Sunan Ibnu Majah, how are the views of the scholars regarding the increase in the descent of faith and immunity and what is the relationship between faith and immunity. This research was conducted to find out how the quality of the Hadith regarding the morning prayer in Sunan Ibnu Majah, how faith affects the body's immunity through the views of Ulama and research. The method used in the research that I will discuss is using the thematic method (Maudu'i), namely by collecting hadiths related to the title of the theme to be studied, and in this study the authors used library research, namely by using references- References from literature that are relevant and in accordance with this study, namely: in the form of writings or books, these sanad Ḥadīṡ fulfill the criteria for sanad shahih. As for the assessment of matan, Ḥadīṡ does not conflict with the Qur'an and Ḥadīṡ shaḥīḥ, does not conflict with reason and law. However, when viewed from a single isnad, the matan of Sunan Ibn Majah above is a dhaif matan. However, after the I'tibar sanad was carried out, the matan of Sunan Ibnu Majah's Hadith above rose to become shahih lighairihi because it was strengthened by the authentic sanad and matan. Thus, Sunan Ibn Majah's Hadith can be used as Hujjah. The relationship between the ups and downs of faith and immunity is that immunity in the body will follow the state of faith in us. Therefore it is highly recommended to strengthen our faith by dhikr, pray 5 times a day and draw closer to Allah so that the Immunity within us can be stable. If all of that is not done it will affect the quality of immunity